An association between bilateral keratoconus in a patient with spondyloocular syndrome and xylosyltransferase II gene mutation - Sara Fathi-Nieto; Rodrigo Butrón-Ruiz; Enrique García-Soler; Ana Hervás-Ontiveros; Amparo Ortiz-Seller (Oman Journal of Ophthalmology, 2022)
Spondyloocular syndrome (SOS) is a rare autosomal-recessive disorder. Since 2015, SOS has been linked to mutations in xylosyltransferase II (XYLT2) locus. Phenotypic features could affect multiple systems, such as sight, hearing, or bones. Herein, we report a case of SOS with multiple bone fractures without trauma, bilateral cataracts, and sensorineural hearing loss. Mutations in XYLT2 gene were detected, and the diagnosis of SOS was made. At the age of 8, the patient presented with progressive vision loss. Slit-lamp examination revealed inferior steepening, apical scarring, and thinning of the cornea. Due to keratoconus suspicion, a corneal tomography was done, confirming the diagnosis of keratoconus. We present the first case of bilateral keratoconus in a patient with SOS.